Surface area estimation for application of wound care. Issue 3 (March 2017) - Spinczyk, Dominik; Wideł, Monika
Abstract: Estimation of surface for application of wound care is one of the important prognostic factors for wound healing. The objective of this study is to measure a surface area estimation for application of wound care. Non-invasive, 3D surface reconstruction methodology using two monocular cameras was implemented and verified. The measurement environment was setup on 10 patients with different kind of wounds. Phantom measurements, with known dimensions, show accuracy of implemented method below 11 percent The patient's measurements has the same accuracy. The implemented method use state of art algorithms and the cheap equipment and can be treated as an auxiliary, more objective method to quantify the wound healing process.